2018
DOI: 10.1002/mdc3.12635
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dystonia‐ataxia Syndromes: Clinical Spectrum, Diagnostic Approach, and Treatment Options

Abstract: Background Dystonia and ataxia are manifestations of numerous disorders, and indeed, an ever‐expanding spectrum of genes causing diseases that encompass dystonia and ataxia are discovered with the advances of genetic techniques. In recent years, a pathophysiological link between both clinical features and the role of the cerebellum in the genesis of dystonia, in some cases, has been proposed. In clinical practice, the genetic diagnosis of dystonia‐ataxia syndromes is a major issue for genetic counseling, progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 90 publications
(115 reference statements)
1
17
0
Order By: Relevance
“…Recent genetic studies suggested the molecular pathways of dystonia and ataxia being closely intertwined. With more than 100 genetic conditions associated with a phenotypic spectrum encompassing both entities, there has been emerging data suggesting that dystonia is a network disorder involving both the cerebellum and basal ganglia—2 closely interconnected structures rather than the disorder related solely to the abnormalities in the basal ganglia. This concept has been supported by clinical studies (cerebellar abnormalities reported in patients with cervical dystonia), by a number of neuroimaging studies including diffusor tensor imaging, tractography, and [18F]‐fluorodeoxyglucose–positron‐emission tomography, and animal studies .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent genetic studies suggested the molecular pathways of dystonia and ataxia being closely intertwined. With more than 100 genetic conditions associated with a phenotypic spectrum encompassing both entities, there has been emerging data suggesting that dystonia is a network disorder involving both the cerebellum and basal ganglia—2 closely interconnected structures rather than the disorder related solely to the abnormalities in the basal ganglia. This concept has been supported by clinical studies (cerebellar abnormalities reported in patients with cervical dystonia), by a number of neuroimaging studies including diffusor tensor imaging, tractography, and [18F]‐fluorodeoxyglucose–positron‐emission tomography, and animal studies .…”
Section: Discussionmentioning
confidence: 99%
“…When family history is suggestive of an autosomal‐recessive pattern of inheritance, Friederich's ataxia (ATX‐FXN), ataxia‐telangiectasia (ATX‐ARL13B, ATX‐ATM), and AOA1 (ATX‐APTX) and 2 (ATX‐SETX) are the top differential diagnoses . It is prudent to remember the reversible causes of ataxia such as vitamin E deficiency (ATX‐TTPA; clues include proprioception loss, pyramidal signs, retinopathy), Refsum's disease (ATX‐PHY; anosmia, retinitis pigmentosa, hearing loss, ichthyosis), or biotin‐thiamine‐responsive basal ganglia disease (mutations in the SLC19A3 gene) . Dystonia may be associated with metabolic disorders such as, for example, Willson's disease (DYT/ATX‐ATP7B; Kayser‐Fleischer ring, liver disease, parkinsonism, myoclonus), neurodegeneration with brain iron accumulation (NBIA; NBIA/DYT/PARK‐CP, NBIA/DYT‐PANK2, NBIA/DYT/PARK‐PLA2G6), lysosomal storage disorders (eg, Pelizaeus Merzbacher disease [ATX/HSP‐GJC2], Niemann‐Pick type C), mitochondrial disorders, and parkinsonian disorders …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations